Intersectionality and Youth Identity Development Research in Europe - Moffitt, Ursula; Juang, Linda P.; Syed, Moin (Frontiers in Psychology, 2020)
The increasing application of intersectionality to the psychological study of identity development raises questions regarding how we as researchers construct and operationalize social identity categories, as well as how we best capture and address systems of oppression and privilege within our work. In the continental European context, the use of the intersectionality paradigm raises additional issues, since “race” was officially removed from the vernacular following the atrocities of WWII, yet racialized oppression continues to occur at every level of society. Within psychological research, participants are often divided into those with and without “migration background,” which can reiterate inequitable norms of national belonging while washing over salient lived experiences in relation to generation status, citizenship, religion, gender, and the intersection between these and other social locations. Although discrimination is increasingly examined in identity development research, rarely are the history and impact of colonialism and related socio-historical elements acknowledged. In the current paper, we aim to address these issues by reviewing previous research and discussing theoretical and practical possibilities for the future. In doing so, we delve into the problems of trading in one static social identity category (e.g., “race”) for another (e.g., “migration background/migrant”) without examining the power structures inherent in the creation of these top-down categories, or the lived experiences of those navigating what it means to be marked as a racialized Other. Focusing primarily on contextualized ethno-cultural identity development, we discuss relevant examples from the continental European context, highlighting research gaps, points for improvement, and best practices.